Rice Production Modeling In Indramayu Using Panel Regression - Yulianto, Safa’at; Anggara, Wahyu (Prosiding University Research Colloquium, 2022)
In Indonesia, the agricultural sector plays an important role in development and the national economy. One of the agricultural commodities that are needed by the community is rice. Rice is a rice-producing commodity which is the main food crop for the Indonesian population. Rice production in Indonesia in 2019 is estimated at 54.60 million tons of Gabah Kering Giling (GKG). Based on data in 2019, West Java occupies the third position as the highest contributor to rice production in Indonesia. Indramayu Regency is the largest contributor to rice production in West Java Province. The results of rice production in Indramayu Regency from 2015-2019 fluctuated every year. To prevent a decrease in rice production in Indramayu Regency, it is necessary to know the factors that affect rice production. In this study, rice production is the response variable (Y). The independent variables (X) are land area (X1), planting area (X2), and harvested area (X3). The data used is secondary data obtained from the Department of Agriculture and Plantation of Indramayu Regency in 2015-2019. Based on analysis using the Panel Data Regression method with the results of the best model used, namely the Fixed Effect Model (FEM)